(untitled) (Global Journal of Science Frontier Research, 2017)
In this paper, we obtained solution of Einstein field equations for Bianchi type VI cosmological model with time dependant cosmological term of the form and . It is observed that cosmological term is decreasing function of time which is consistent with results from recent supernova Ia observations. Also, it is noted that the model approaches to isotropy for = 1. All the physical parameters are calculated and discussed.